Mitigating the negative impacts of marine invasive species – Sargassum muticum - a key seaweed for skincare products development - Susano, Patrícia (2022)
Sargassum muticum is a highly invasive species, threatening marine biodiversity worldwide. One strategy to reduce marine invaders’ impacts is to promote their use as valuable biomass for new products development. On the other hand, there is a rising conscience of natural compounds importance as health promoters. The present work was designed to sustainably use the marine invasive seaweed S. muticum collected off the Portuguese shore for novel skincare products. The antioxidant, anti-enzymatic (collagenase, elastase, hyaluronidase, tyrosinase), antimicrobial (Staphylococcus epidermidis, Cutibacterium acnes, Malassezia furfur), photoprotective, and antiinflammatory properties of five fractions (F1–F5) obtained by a sequential extraction of S. muticum were evaluated. The diethyl ether fraction (F2) demonstrated the most promising results, with the highest antioxidant and photoprotective capacity, reducing reactive oxygen species (ROS) production promoted by UVA and UVB radiation in 3T3 cells. On the other hand, the ethyl acetate fraction (F3) exhibited the highest anti-enzymatic capacity, inhibiting the activities of collagenase, hyaluronidase and tyrosinase (IC50 of 97.5, 23.7 and 72.3 μg/mL, respectively). Moreover, fractions from S. muticum showed anti-inflammatory potential by reducing tumor necrosis factor – α and interleukin-6 release. A chemical screening by 1H NMR of S. muticum fractions evidenced signals that can be attributed to the presence of different chemical classes, including lipids, pigments, amino acids, polyphenols, and sugars, being related to the observed multitarget properties. This work highlights a strategic valorisation of S. muticum as a source of treasured ingredients for skincare applications.